Dissecting causal associations of type 2 diabetes with 111 types of ocular conditions: a Mendelian randomization study - Chen, Rumeng; Xu, Shuling; Ding, Yining; Li, Leyang; Huang, Chunxia; Bao, Meihua; Li, Sen; Wang, Qiuhong (Frontiers in Endocrinology, 2023)
Background: Despite the well-established findings of a higher incidence of retina-related eye diseases in patients with diabetes, there is less investigation into the causal relationship between diabetes and non-retinal eye conditions, such as age-related cataracts and glaucoma. Methods: We performed Mendelian randomization (MR) analysis to examine the causal relationship between type 2 diabetes mellitus (T2DM) and 111 ocular diseases. We employed a set of 184 single nucleotide polymorphisms (SNPs) that reached genome-wide significance as instrumental variables (IVs). The primary analysis utilized the inverse variance-weighted (IVW) method, with MR-Egger and weighted median (WM) methods serving as supplementary analyses. Results: The results revealed suggestive positive causal relationships between T2DM and six ocular conditions (P < 0.05), including “Senile cataract” (OR= 1.07; 95% CI: 1.03, 1.11; P=7.7710-4), “Glaucoma” (OR= 1.08; 95% CI: 1.02, 1.13; P=4.8110-3), and “Disorders of optic nerve and visual pathways” (OR= 1.10; 95% CI: 0.99, 1.23; P=7.0110-2). Conclusion: Our evidence supports a causal relationship between T2DM and specific ocular disorders. This provides a basis for further research on the importance of T2DM management and prevention strategies in maintaining ocular health.